WR 123 OER Resources - Kathy Austin; Joyce Bower (Linn-Benton Community College, 2021)
Introduces informative and analytical writing supported by research. Students design a research plan, use primary and secondary sources critically, develop research methods, use proper documentation and develop writing strategies for longer papers.